An Integrated Approach to InService Training Efficiency Factors (Eurasian Scientific Herald, 2022)
This article defines informatization of the education system in our country is a global social process, the need for creative work, focused on the creative, targeted use of information resources: data collection, processing, use of constantly evolving scientific and methodological, creative approaches, information, pedagogical technologies, education, integration of production technologies. Teachers and educators working in the system of in-service training, mastering modern information and communication technologies, tools, creative approaches in pedagogical activities systematically improve their knowledge, skills and abilities.